STUDENTS' AND TEACHERS' PERCEPTIONS OF USING ELECTRONIC TEXTBOOKS IN EDUCATIONAL PROCESS - Olga Trishchuk; Nadija Figol; Tetiana Faichuk; Svitlana Fiialka (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2020)
The research evaluates the effectiveness of using electronic textbooks in educational process compared to printed publications. The advantages and disadvantages of introducing e-textbooks in higher education institutions are determined. The problems that students face while working with e-textbooks are outlined. Based on the literature analysis, the authors claim that e-textbooks are more convenient and are being increasingly used in the educational process. A standardised questionnaire including 17 questions was developed by authors to determine students' and teachers' perceptions of using e- textbooks in educational process. Data analysis tools comprise the methods of mathematical and descriptive statistics. According to the survey, users want to get cheap but high-quality e-textbooks, with a high level of production, without errors, and with completeness of information. The price and the quality play a crucial role in decision making. Also, the criterion of e-textbooks friendliness is of great importance, including ease of search, the ability to navigate by hyperlinks, and adaptive layout for different devices. The problem of standardisation of e-textbooks may be the subject of further research and practical development.